Activity of the aurora kinase B inhibitor AZD1152 in acute myeloid leukaemia - Grundy, Martin (2012)
Aurora kinases play an essential role in orchestrating chromosome alignment, segregation and cytokinesis during mitotic progression, with both aurora-A and B frequently over-expressed in a variety of human malignancies including those of leukaemic origin. Acute myeloid leukaemia (AML) is a heterogeneous clonal disorder of haematopoietic progenitor cells whose prognosis is particularly poor and where standard induction therapy has changed little over the past thirty years. This thesis evaluated the effects of AZD1152-hQPA (barasertib-hQPA), a highly selective inhibitor of aurora-B kinase, in AML cell lines and primary samples. Inhibition of phospho-Histone H3 (pHH3) on serine 10 can be used as a biomarker for AZD1152-hQPA activity and an assay was optimized to measure pHH3 in our cell lines and primary samples. AZD1152-hQPA inhibited pHH3 in our cell lines resulting in polyploid cells, apoptosis, and cell death, irrespective of cellular p53 status.